Teacher Strategies in the Implementation of Distance Learning During the Covid-19 Pandemic - Ida Ayu Hani Erlina; Rahmad Rafid (research, training and philanthropy institution Natural Aceh, 2021)
Abstract: This study aims to examine teacher strategies in implementing distance learning during the COVID-19 pandemic. The research method used a descriptive qualitative approach to the type of case study research and used a phenomenological paradigm. Because seeing the current pandemic conditions that are still ongoing. So, the data collection technique in this study was carried out online through a questionnaire distributed via google form, by asking several questions related to the problem to be studied. Then, for informants in this study were some school teachers from several regions in Java and Lampung and from three levels of education units, namely SD, SMP, and SMA. The data analysis used in this research is descriptive analysis which aims as a tool to map data and reveal the meaning behind the data that has been obtained. The results showed that the distance learning strategies used by teachers during the pandemic were predominantly effective and smooth. However, there were several obstacles that were found during the learning process, such as poor network connections and a lack of student motivation to take part in distance learning. Therefore, there is a need for effective self-development of teachers on an ongoing basis to improve competence. The role of government through policies made is also very important as a forum for increasing human resources Abstrak: Penelitian ini bertujuan untuk mengkaji strategi guru dalam pelaksanaan pembelajaran jarak jauh selama masa pandemi COVID-19. Metode Penelitian menggunakan pendekatan kualitatif deskriptif dengan jenis penelitian studi kasus dan menggunakan paradigma fenomenologi. Karena melihat kondisi pandemi yang sekarang ini masih berlangsung. Maka, teknik pengambilan data dalam penelitian ini dilakukan secara online melalui kuesioner yang disebarkan melalui google form, dengan mengajukan beberapa pertanyaan terkait dengan masalah yang akan diteliti. Kemudian, untuk informan dalam penelitian ini adalah beberapa guru sekolah dari beberapa daerah yang berada di Pulau Jawa dan Lampung dan dari tiga tingkat satuan pendidikan yaitu SD, SMP, dan SMA. Analisis data yang digunakan dalam penelitian ini adalah analisis deskriptif yang bertujuan sebagai alat untuk memetakan data dan mengungkap makna dibalik data yang telah didapatkan. Hasil penelitian menunjukan bahwa strategi pembelajaran jarak jauh yang digunakan oleh guru selama masa pandemi secara dominan berjalan efektif dan lancar. Tetapi, ada beberapa kendala yang ditemukan selama proses pembelajaran berlangsung seperti koneksi jaringan yang kurang baik serta kurangnya motivasi siswa dalam mengikuti pembelajaran jarak jauh. Oleh karena itu, perlu adanya pengembangan diri secara efektif pada guru secara berkelanjutan untuk meningkatkan kompetensi. Peran pemerintah melalui kebijakan yang dibuat juga sangat penting sebagai wadah dalam meningkatkan sumber daya manusia.